Synthesis of cellulose derived from bamboo (Bambusa Vulgaris) for 2-d application: biofoam - Zahidan, Nur Salsabilla (2020)
Environmental concerns have led to a push to displace non-biodegradable products that are made from non-renewable resources with biodynamic bamboo-based material (Bambusa vulgaris). An indication of such a substitute is analysis towards the use of bamboo fibers as a raw material for biodegradable foams. Cellulose biofoam (CBF) is composed primarily of natural composites of bamboo cellulose and amylopectine starch made up of potato. The purpose of this study is to research the morphology of the bamboo cellulose fiber composite mixture of bio-foam. This thesis would illustrate how lightweight microfibril-based foams can be treated. Lightweight and highly soluble foams have been effectively formulated using cellulose fiber combined with amylopectin starch as a copolymer. Blowing agents and other additives. Developed macroporous cellulose biofoam has been identified by a number of methods, including compressive analysis energy dispersive X-ray (EDX) and thermogravimetric analysis (TGA). The morphology and microstructure of the porous materials have been studied by electron scanning microscopy (SEM) and optical light microscopy. It was found that the introduction of cellulose fibres during the foaming process was necessary to create the three-dimensional polymer foams. Using cellulose fibres has potential as a foam stabiliser because it obstructs the drainage of liquid from the film region while simultaneously acting as reinforcing agent in the polymer foam. The optimal percentage of bamboo cellulose fibre content should be 10wt% to get the best result on mechanical properties. The optical light microscope and scanning electron microscope (SEM) images show that biofoam composites have homogeneous cell dispersion. Density of composites decreased from 0% wt%, 10wt% to 20wt% as result of the increase in bamboo cellulose content from 1.21 g/cm3, 0.49 g/cm3 to 0.46 g/cm3 respectively. Mechanical properties such as Youngs Modulus of the samples changed substantially with the increase of cellulose microfibril content from 6.91 MPa to 78.74 MPa (0 wt% to 10 wt% of cellulose microfibril). However, thermogravimetric analysis (TGA) data showed only slight improvement in the thermal stability of the biofoam by the addition of cellulose fibre.